IMPLEMENTASI REST API PADA SISTEM PENDATAAN KAPAL MENGGUNAKAN LARAVEL 9 DAN NUXTJS - Saputra, Laurensius Sirwanti; Fery Herdiyatmoko, Hendrik (Ninety Media Publisher, 2024)
The development of technology, especially computers, is increasingly rapid and has become a daily human need. At the Palembang Type A Class I Navigation District, computer technology plays an important role in improving effective and efficient performance. This district is tasked with overseeing shipping telecommunications, disseminating shipping weather information, and overseeing the implementation of shipping lanes and telecommunications. The previous ship entry and exit data collection system was still manual using Microsoft Word for daily, monthly, and weather reports. To overcome this problem, a Website-based ship entry and exit data collection system was created using REST API Web Service technology. REST API facilitates JSON-based information exchange over the Internet network, allowing data integration between internal and external parties. This system was developed with Laravel 9 Framework as the Backend and NuxtJs as the Frontend. The results showed that the Website-based ship entry and exit data collection system with REST API technology was successfully implemented and ran according to the provisions and format of ship data collection at the Palembang Type A Class I Navigation District.